Islamic Education at Multicultural Schools - Irham Irham (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2017)
This article aims to explain the roles of PAI (Pendidikan Agama Islam/Islamic Education) at multicultural schools. It was the results of the field research by using a qualitative method. The research was conducted at SMA (Sekolah Menengah Atas/Senior High School) Plus Pembangunan Jaya Bintaro Tangerang. The school was selected because its students had diversity of backgrounds, and the school had committed to develop the multicultural insights. Data of research were obtained through interview, observation, and documentation. The results showed that PAI had the roles as the pluralism moral activator to students. PAI was applied in the educational process to form students’ multicultural attitude and thought. There were two underlying findings, namely: type of inclusive educators and design of multicultural curriculum.